PENDEKATAN PEMBANGUNAN DAMPAK RENDAH UNTUK SUMUR RESAPAN DAN ANALISIS BIAYA INVESTASINYA DI WILAYAH PERKOTAAN - Oktavia Kurnianingsih; Delista Putri Deni (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2025)
Flood, economic and environmental problems in the implementation of sustainable drainage systems in developing countries are very complex. The use of infiltration wells as an alternative method to infiltrate groundwater as one of the low-impact developments. Infiltration wells function to accommodate and absorb water into the soil. The high growth of the population led to an increase in development. Development that has an impact on the reduction of catchment areas, this research aims to approach the low-impact development strategy (LID) in urban areas in developing countries. Sustainable drainage development is still limited to the regional budget. Cost analysis was carried out by hydrological modeling for infiltration well planning. Infiltration wells are chosen as sustainable drainage. Infiltration wells can reduce the risk of flooding and drought. Discharge analysis with the Rational Method. The planning of the dimensional infiltration well was calculated using the Sunjoto formula and the basic design using filitration. The infiltration well model is planned with a depth of 1.7 m and a diameter of 1 m. The cost of making an infiltration well is Rp 2,125,500 for one well. This research is expected to help decision-making in sustainable urban water management. Flood and drought mitigation balancers and costs.